Coronary artery bypass grafting in an achondroplastic dwarf. - Balaguer, J M (1995)
To our knowledge, coronary bypass for complications of coronary artery disease in achondroplasia has not previously been described. Achondroplasia, in and of itself, is not a contraindication to coronary bypass. Although the anatomic reserve of saphenous vein is less in achondroplastic dwarfs than in people of normal stature, that vessel and the internal mammary artery can be harvested in routine fashion. A 60-year-old woman with several risk factors for coronary artery disease underwent successful bypass surgery, which included the use of both a saphenous vein and the left internal mammary artery.